2011
DOI: 10.3109/0886022x.2011.641515
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Abnormalities and Oxidized LDL in Chronic Kidney Disease Patients on Hemodialysis and Peritoneal Dialysis

Abstract: Dyslipoproteinemia and oxidative modification of low-density lipoprotein (oxLDL) contribute to the development of oxidative stress and atherosclerosis in chronic kidney disease (CKD). On the contrary, high-density lipoprotein cholesterol (HDL-C), especially HDL3-C subtype, has protective effect against oxidative damage. There is limited evidence referring HDL-C subclass levels in patients on dialysis. This study was designed to compare lipid abnormalities and oxLDL levels in hemodialysis (HD) and peritoneal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…The disulfide/native thiol levels were also different between the three groups; the disulfide/native thiol levels were slightly higher in the transplantation and PD groups compared to the HD group. While these results are consistent with few other previous studies, increased levels of oxidative stress in HD compared to those in PD have also been reported in some studies (20)(21)(22)(23)(24). We believe that the increased oxidative stress observed in the PD patients (compared to those in the HD patients) in our study may have been caused by inflammatory responses.…”
Section: Discussionsupporting
confidence: 55%
“…The disulfide/native thiol levels were also different between the three groups; the disulfide/native thiol levels were slightly higher in the transplantation and PD groups compared to the HD group. While these results are consistent with few other previous studies, increased levels of oxidative stress in HD compared to those in PD have also been reported in some studies (20)(21)(22)(23)(24). We believe that the increased oxidative stress observed in the PD patients (compared to those in the HD patients) in our study may have been caused by inflammatory responses.…”
Section: Discussionsupporting
confidence: 55%
“…The current study shows that, although the level of 8-OHdG was higher in both prevalent HD and PD patients than in control subjects, dialysis modality (and dialysis vintage) contributed to explain the variance of oxidative stress as assessed by plasma 8-OHdG. Two recent studies comparing oxidative stress in various dialysis modalities showed increased levels of advanced oxidation protein products in HD patients compared with PD patients (18,19), and three other studies found similar or lower levels of oxidative stress markers (advanced oxidation protein products, myeloperoxidase, and 8-OHdG) in HD patients than in PD patients (20)(21)(22). Although the HD procedure might induce repetitive bouts of oxidative stress, primarily through dialyzer membrane incompatibility and endotoxin contaminants (28,29), glucose degradation products in glucose-based PD fluids are also thought to increase oxidative stress (30).…”
Section: Discussionmentioning
confidence: 96%
“…Also, it is not known whether oxidative stress varies with dialysis modality. In a few studies, increased levels of oxidative stress have been reported to be associated with hemodialysis (HD) compared with peritoneal dialysis (PD) (18,19), but other studies showed the opposite results (20)(21)(22).…”
mentioning
confidence: 99%
“…Increased oxidative damage in patients on chronic haemodialysis treatment has been considered to contribute to their increased cardiovascular risk [47][48][49], which cannot be completely explained by traditional cardiovascular risk factors and may be ameliorated with antioxidant intervention. Despite evidence for harmful effects in the general population of high doses of some common supplements (β-carotene, vitamin E, vitamin A) [50,51], there is evidence, although limited, that chronically haemodialysed patients could benefit from the use of antioxidants to prevent cardiovascular complications [52,53].…”
Section: Discussionmentioning
confidence: 99%